2018
DOI: 10.1103/physrevb.97.104412
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of shot noise in double barrier magnetic tunnel junctions

Abstract: Shot noise reveals spin dependent transport properties in a magnetic tunnel junction(MTJ). We report measurement of shot noise in CoFeB/MgO/CoFeB/MgO/CoFeB double barrier magnetic tunnel junctions(DBMTJs), which shows a strong temperature dependence. The Fano factor used to characterise shot noise increases with decreasing temperature. A sequential tunneling model can be used to account for these results, in which a larger Fano factor results from larger spin relaxation length at lower temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, the shot noise in the tunnel junction is not only modulated by the intensity of Rashba coupling and the added external electric field but also depends on the quantum size [23][24][25]. Wu et al also confirmed these results when they studied the tunneling of spin electrons through the dilute magnetic semiconductor/semiconductor junction [26], while Niu et al pointed out that temperature has a great influence on shot noise [27].…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the shot noise in the tunnel junction is not only modulated by the intensity of Rashba coupling and the added external electric field but also depends on the quantum size [23][24][25]. Wu et al also confirmed these results when they studied the tunneling of spin electrons through the dilute magnetic semiconductor/semiconductor junction [26], while Niu et al pointed out that temperature has a great influence on shot noise [27].…”
Section: Introductionmentioning
confidence: 91%
“…Based on the dilute magnetic semiconductors/semiconductor junctions and the junctions with step barrier, the results in references [28,29] confirmed that shot noise has a strong dependence on the quantum size effect and the applied electric field. In addition, Niu et al reported that the shot noise in a double-barrier magnetic tunnel junction has a strong dependence on temperature [30].…”
Section: Introductionmentioning
confidence: 99%